Lee Sissom: capstone - Sissom, Lee, artist (Colorado State University. Libraries, 2025)
The artist's statement: Lee Sissom is a multimedia artist and graphic designer pursuing a career in health communications. They pride themselves on being versatile, with the ability to create everything from deeply expressive personal pieces to minimalistic corporate designs. Their approach to design is rooted in collaboration. They often look for feedback and revisions from their team, and they love learning about others' perspectives on their work to make sure that it accurately conveys themselves or the brand that they are representing. Lee is trained in the Adobe Suite, including Illustrator, InDesign, After Effects, and Photoshop. They are familiar with commercial print processes and preparing files for merchandise. Some of their favorite traditional mediums are gouache and acrylic paint. They enjoy fusing their passion for multiple mediums with their design work. Their passion for health communications runs deep. While they found it challenging, they faced health issues of their own that became a large opportunity for growth and self-reflection. They aim to help others through similar experiences. They believe that every design is the ability to influence consumers, and health is a field that can easily feel convoluted. They enjoy adapting information to help audiences easily digest complex information.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design